Interface engineering in 2D materials for SERS sensing - Zhao, Shaoguang; Zhao, Yu; Tao, Li (Frontiers in Materials, 2023)
In recent years, the use of 2D materials as surface-enhanced Raman scattering (SERS) active substrates has been extensively investigated. This mini review emphasizes the tunable interface characteristics of 2D materials as SERS substrates. Notably, 2D materials exhibit a wealth of tunable properties, encompassing energy levels, band structures, and interlayer coupling, which confer upon them significant potential as versatile SERS substrates. We summarize the recent advances in tunable 2D materials as SERS active substrates, providing guidance for future research in developing tunable multifunctional molecular sensors based on 2D materials.